Performance Auditing of State Programmes of the Russian Federation - Viktoriya Aleksandrovna Vuimo (Учёт. Анализ. Аудит, 2019)
The article essentially describes the essence of performance auditing in the framework of the evolution of the state financial control and its role in the transition to the program-target method of budget planning. Besides, we will consider the use of performance auditing in the implementation of State programmes of the Russian Federation, and denote our point of view, whether the auditing of State programs and performance efficiency auditing are synonyms. As a result, the authors have summarized the current state of performance auditing and expressed their point of view regarding the possible use of the specified kind of auditing in assessing the performance and its elements (economy, efficiency and effectiveness) of State (targeted) programmes. The authors have also revealed its significant benefits for the management of these programmes at different stages of development: from design to implementation.